A mini-overview of single muscle fibre mechanics: the effects of age, inactivity and exercise in animals and humans (Swiss Medical Weekly, 2017)
Many basic movements of living organisms are dependent on muscle function. Muscle function allows for the coordination and harmonious integrity of movement that is necessary for various biological processes. Gross and fine motor skills are both regulated at the micro-level (single muscle fibre level), controlled by neuronal regulation, and it is therefore important to understand muscle function at both micro- and macro-levels to understand the overall movement of living organisms. Single muscle mechanics and the cellular environment of muscles fundamentally allow for the harmonious movement of our bodies. Indeed, a clear understanding of the functionality of muscle at the micro-level is indispensable for explaining muscular function at the macro-(whole gross muscle) level. By investigating single muscle fibre mechanics, we can also learn how other factors such Ca2+ kinetics, enzyme activity and contractile proteins can contribute to muscle mechanics at the micro- and macro-levels. Further, we can also describe how aging affects the capacity of skeletal muscle cells, as well as how exercise can prevent aging-based sarcopenia and frailty. The purpose of this review is to introduce and summarise the current knowledge of single muscle fibre mechanics in light of aging and inactivity. We then describe how exercise mitigates negative muscle adaptations that occur under those circumstances. In addition, single muscle fibre mechanics in both animal and human models are discussed.